EDUCATIONAL PARTNERSHIP: EFFECTIVE COLLABORATION OF PARENTS AND MADRASAH FOR STUDENT SUCCES - Hasanah, Uswatun; Muali, Chusnul; Rofiki, Moh.; Fajri, Zaenol; Widat, Faizatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Transparency and open communication are the basis for joint decision-making and the creation of inclusive policies responsive to diverse students' needs. Empowering parents as partners involves participation in learning programs, open discussions, and introducing Islamic values at home. The conclusion highlights that the educational partnerships at MI Hasanuddin not only improve the quality of education but also form a holistic environment that supports students' character development and success. This research uses a qualitative case study type method by conducting research aimed at describing problems and analyzing the problems that occur. Researchers collected data through several stages, such as observation and direct observation at the research site. Interview interviewing several informants at the research location. Observation, visiting research locations. Documentation study, analyzing documents related to research. Based on the research results show that several programs or processes carried out by madrasas involving parents include: (1) Partnership at MI Hasanuddin is reflected in the active participation of parents in various aspects of children's education. (2) MI Hasanuddin's transparency and open communication with parents. (3) Joint Decision Making, MI Hasanuddin provides space for parents to be involved in educational decision-making. (4) Empowering Parents as Partners MI Hasanuddin involves parents as observers and considers them partners in shaping children's education.